Pengaruh Model Pembelajaran Make A Match dan Picture and Picture terhadap Hasil Belajar Bahasa Arab - Wirda, Wirda Wahyuni; Sanjaya, Budi; Prihartini, Yogia (Al-Miskawaih: Journal of Science Education, 2022)
This study aims to analyze the effect of the Make a Match and Picture and Picture learning models on students' Arabic learning outcomes. This research is a quantitative study using a quasi-experimental pretest-posttest control group design. The data collection technique used is: test. Data analysis requirements test techniques used are: data description, basic assumption test and classic assumption test. The sampling technique in this study used a purposive sampling technique. This study used three classes, namely two experimental classes and one control class. The results showed 1) there was an increase in students' Arabic learning outcomes after following the Make a Match learning model 2) there was an effect of the Make a Match learning model on students' Arabic learning outcomes 3) there was an increase in students' Arabic learning outcomes after following the Picture and Picture Penelitian ini bertujuan untuk menganalisis pengaruh model pembelajaran Make a Match dan Picture and Picture terhadap hasil belajar bahasa Arab siswa. Penelitian ini merupakan penelitian kuantitatif menggunakan desain quasi eksperimen pretest-posttest control group design. Teknik pengumpulan data yang digunakan yaitu: tes. Teknik uji persyaratan analisis data yang digunakan yaitu: deskripsi data, uji asumsi dasar dan uji asumsi klasik. Teknik pengambilan sampel dalam penelitian ini dengan menggunakan teknik purposive sampling. Penelitian ini menggunakan tiga kelas yaitu dua kelas eksperimen dan satu kelas kontrol. Hasil penelitian menunjukkan 1) terdapat peningkatan hasil belajar bahasa Arab siswa setelah mengikuti model pembelajaran Make a Match 2) terdapat pengaruh model pembelajaran Make a Match terhadap hasil belajar bahasa Arab siswa 3) serta terdapat peningkatan hasil belajar bahasa Arab siswa setelah mengikuti model pembelajaran Picture and Picture